Activities in the zone of proximal development between the development of motor skills and school readiness: studies in kindergartens - Patrizia Tortella; Guido Fumagalli (Pensa MultiMedia, 2015)
The growing number of children with impairment in executive functions and the growing increasing of sedentary behavior, estimated to be a major culprit of obesity and metabolic diseases, call for intensive efforts for correction of these worldwide problems affecting the quality of life. Recent studies highlight that executive functions can be incremented early and during life and suggest that physical activity may be an important tool to reach this goal. Educator has thus a great responsibility and recent data indicate that kindergarten may represent a new and up-to-now little considered educational tool. To involve and share with teachers these new aspects of education, an action-research was carried out with 100 teachers of Treviso (Italy), 51 kindergartens. Teachers were given instructions by means of a book prepared for the project and containing suggestions for the organization of physical activity lessons in kindergartens. After the use of the book, which also included stimuli for evaluation of the activities and their impact on children, teacher were involved in discussions and focus groups from where important considerations emerged about education directed at fostering motor and cognitive development of pupils. Our study indicate that implementation of results of scientific studies in daily activities requires direct participation of educators starting from their knowledge and perception of the realty of the teaching environment.